Dampak Penggunaan Gadget Terhadap Sikap Simpati Dan Empati Antar Mahasiswa Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta (STITMA) - Muhammad Zarly Haqiqi; Hilalludin Hilalludin; Rafly Billy Limnata; Dibi Nicklany (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to identify the impact of gadget use on the sympathy and empathy attitudes of students at Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta. The background of this study is rooted in the widespread use of gadgets among students, which affects social interactions and the ability to understand others' feelings. The research method employed is literature review, gathering data from various literary sources such as books, academic journals, and research reports. Findings indicate that excessive gadget use reduces face-to-face interactions, hindering the development of sympathy and empathy among students. Those who communicate more through social media tend to be less aware of their surroundings and struggle to understand and feel others' emotions. The implications underscore the importance of raising awareness about the negative impacts of gadgets and regulating non-academic gadget use. Encouraging more direct interactions and providing social skills training can help students develop better sympathy and empathy attitudes, thereby maintaining the quality of their social relationships in the digital age.